Enterprise Architecture Planning Using TOGAF ADM (Case Study: Kantor Desa Tengah Pancur Batu) - sipayung, liske (Cattleya Darmaya Fortuna, 2025)
The Central Village Office of Pancur Batu is a government institution that operates in the village in the Pancur Batu sub-district area of Deli Serdang Regency. The government Pancur Batu Tengah Village has not implemented Information System in carrying out its duties, this can be seen from the obstacles faced by the Village Government. obstacles faced by the Village Government. The obstacles faced are often hoarding old data, making it difficult when it will be recorded again, even usually there is data that is lost so that it requires a system that can help store data. help with data storage. The purpose of this research is to provide direction to be able to implement an information system for data storage. performance in the future. The method used in the development of enterprise architecture this time is the TOGAF method. architecture development this time, namely the TOGAF ADM (The Open Group Architecture Framework) by using 3 (three) phases out of 9 (nine) phases, Preliminary Phase, Architecture Vision Phase and Business Architecture Phase. Phase. This research will produce a blueprint and provide a roadmap using the elements in TOF ADM. using the existing elements of TOGAF in the Village Office in order to implement a performance information system for the Pancur Batu Central Village Office in the future. in the future.